Big Data Ecosystems in Re-distributed Manufacturing: Past and Future - Zaki, Mohamed; Neely, Andy; Friedrich Tepel, Matthias; Theodoulidis, Babis; Shapira, Philip (Cranfield University, 2017)
This is one of five feasibility studies reports produced by the RECODE Network
Keywords: 'Consumer Goods'; EPSRC; 'RECODE Network'; 'Manufacturing Engineering not elsewhere classified'; 'Manufacturing Processes and Technologies (excl. Textiles)'; 'Manufacturing Management'; Re-distributed Manufacturing'; 'Big Data'